The tale of 'Semar Mbangun Kahyangan': symbolic message in Javanese society - Ratri Atmoko; Juliana Murniati; Hana Panggabean; Rustono Farady Marta; Rüdiger Trimpop; Monika Eigenstetter (Jurnal Studi Komunikasi, 2024)
The Cembengan ceremony is a Slametan tradition commonly practised by sugar factories before the milling season. This ritual is a prayer for high productivity and excellent safety performance in the workplace during the milling process. Wayang is then played as the highlight of the event with Semar Mbangun Kahyangan as one of the usually performed stories. This study seeks to answer this question: What are the traditional safety concepts staged in the Slametan tradition in the workplace? This study used a content analysis approach to identify, analyse, and categorise the recording data of a wayang performance with the story of Semar Mbangun Kahyangan performed by Ki Dalang Hadi Soegito. This study has found that besides human destiny had been written by God, the meaning of Safety can be pursued through a multidimensional harmony, known as manunggaling kawula-Gusti (vertical harmony), silaturahmi (horisontal harmony), the harmony among five knights of Pandawa as a symbol of the physical harmony of five senses (sight, hearing, taste, smell, and touch) and psychological-spiritual harmony. The second finding is that a safety attitude is fostered in line with human development, which is symbolised in Wayang's storyline, first, on the Pathet Enem (infancy to adolescent) safety attitude generated by right-wrong consideration. Second, a safety attitude is an ethical decision within Pathet Sanga (early to middle adulthood). Last, at Pathet Mayura (late adulthood), a safety attitude is a spiritual achievement.